Aufwachsen in unübersichtlichen Zeiten: Die Bedeutung von Pädagogen als Berater und Lebensbegleiter von Jugendlichen - Graumann, Olga (International Dialogues on Education Journal, 2017)
The young are the future of society, they are subjected to continuous change, complex, contradictory and diverse and can no longer be considered in a national context only. Through two examples, four crucial developmental challenges with which young people are faced („educating and qualifying“, „dissolving and forging new alliances“, „using media“, „world-oriented acting and political participation“) are examined more closely. The role of educators as advisors and lifelong companions is the focus here. One of the examples addresses the developmental tasks of „educating and qualifying“ as well as „dissolving and forging new new alliances“. It describes and shows how, depsite an extremely difficult childhood and youth, this young person was able to build a future with the support of resilience processes. The second chosen example is that of a youth running amoc in July 2016 in Munich; this pertains to the developmental tasks of „using media, world-oriented acting and political participation“. In particular, the role of the professional educator as advisor is emphasized in this case. The young do not fail primarily because of societal pressures but rather because of the actions of adults.